Cryptocurrencies and tokenization of assets: the managerial implications of a new financial reality - Pizzolato, Luca (2022)
Cryptocurrency and tokenization of assets is a phenomenon that is yet to change many sectors in the economy. Already, its impact has had a significant effect on many financial markets. Cryptocurrencies are more than just a means of payment and transactions. The technology behind it, blockchain, has an even greater impact because it can be adopted even beyond the financial sector. The evolution of tokens and their popularity in the financial sector has had both positive and negative implications on the financial markets and companies. This research seeks to show the managerial implications of cryptocurrency and tokenization of assets. The present dissertation aims to address this gap because of the need for regulation of the sector. To understand the managerial implications of cryptocurrency and tokenization of assets, it is essential that we first understand what the two aspects are and how they operate. Later in this document, we shall observe that Bitcoin is currently the most popular cryptocurrency, although various types exist. At its inception in 2008, there were only about 50 coins in circulation, which has since evolved. Although blockchain technology had long since been invented, it only became popular with Bitcoin. The technology has three versions premised on virtual currency, smart contracts, and other sectors beyond finance and markets. This technology operates through complex algorithms and computers interconnected to minimize the possibility of fraud and hackings. Using companies like PayPal and eBay, valuable assets can be tokenized and traded as well. Blockchain is also popular for its ability to track records. The data is public and easily accessible. However, the privacy and anonymity of persons are also emphasized. Research was carried out using a qualitative method. This was done by reviewing and analyzing past literature on cryptocurrencies and their general impact on the economy. The pros and cons of using cryptocurrency were also examined to form a clear opinion on its economy usage. It was found that cryptocurrency and tokenization of assets guarantee security, are efficient for payment and promote transparency for business. However, it has limitations, such as the increased risk of fraudsters and illegal transactions.